2017
DOI: 10.1055/s-0037-1604082
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Outcomes of Leech Therapy for Venous Congestion in 87 Patients

Abstract: Background We aimed to report the outcomes associated with leech therapy and to identify risk factors associated with reconstructive failure. Methods We retrospectively reviewed cases of flap reconstruction or replanted appendages that required leech therapy over an 8-year period at the Duke University Medical Center. Using logistic regression, we assessed the association of risk factors with reconstructive failure. Results The study cohort included 87 patients which correspond to 2.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Regarding the efficacy of leech therapy in dealing with congested flaps, in our study, there is high rate of success in relieving congestion and flap survival. The mean survival rate was 88.25% in the 20 cases under the study, while Cornejo et al 4 showed a slightly lower rate of salvage (about 60.9%), considering success as there was no flap loss or partial flap loss requiring further reconstructive procedures. On the other hand, Whitaker et al 12 showed that medical leeches salvaged the reconstructed congested flaps in 216 of the 279 cases (77.4%) and in congested free flaps, it salvaged 61 of 74 cases (82.4%).…”
Section: Discussionmentioning
confidence: 78%
“…Regarding the efficacy of leech therapy in dealing with congested flaps, in our study, there is high rate of success in relieving congestion and flap survival. The mean survival rate was 88.25% in the 20 cases under the study, while Cornejo et al 4 showed a slightly lower rate of salvage (about 60.9%), considering success as there was no flap loss or partial flap loss requiring further reconstructive procedures. On the other hand, Whitaker et al 12 showed that medical leeches salvaged the reconstructed congested flaps in 216 of the 279 cases (77.4%) and in congested free flaps, it salvaged 61 of 74 cases (82.4%).…”
Section: Discussionmentioning
confidence: 78%
“…28,29 Leeches can also be used as an adjunct therapy for select cases of venous congestion when the flap has an inherently insufficient venous outflow system; leeches are not routinely used for free flap salvage when there is a concern for acute thrombosis of the venous anastomosis as we rely on exploration and reestablishing venous outflow. [30][31][32] Furthermore, they are of minimal efficacy when used in larger flaps such as those in our cohort with an average size of 300cm 2 . 31,32 Interestingly, vein size mismatch was more prevalent in the first era than the second era (1997-2016) of time recorded in this study (60.0% vs. 40.0%; p ¼ 0.029).…”
Section: Discussionmentioning
confidence: 84%
“…Prevention of flap necrosis is the most common indication for hirudotherapy in plastic surgery; however, the use of leeches for replantation of digits, lips, ears, nipples, nasal tips, and penises have all been documented. 2,9,[13][14][15][16] Flap necrosis secondary to venous congestion can progress within a mere 3 hours, and success of leeching depends on provision of sufficient temporary venous outflow while neovascularization of the flap occurs. [17][18][19] In the most recent systematic review of the success of hirudotherapy in plastic and reconstructive surgery, Whitaker et al demonstrated a total tissue salvage rate of 78%, with only 22% of tissues treated with medical leeches ultimately requiring resection.…”
Section: Applications To Plastic Surgerymentioning
confidence: 99%
“…13 Other studies indicate a slightly lower rate of salvage at 60.9%, considering success as no flap loss or partial flap loss not requiring further reconstructive procedures. 14 Figure 2 shows the best practices from the following information.…”
Section: Applications To Plastic Surgerymentioning
confidence: 99%
See 1 more Smart Citation